Heart Failure as the Initial Presentation of Anomalous Left Coronary Artery From the Pulmonary Artery. (March 2022) - Rao, Suman; Pathmanathan, Anojan; Khan, Alisha; Malik, Muhammad; Chaudhuri, Debanik; Ford, Timothy; Byrum, Craig; Smith, Frank
Coronary arteries arising from the pulmonary artery have an incidence of 0.002% in the general population. We present a 29-year-old woman who presented to our hospital with acute decompensated heart failure and atrial fibrillation with a rapid ventricular rate. She underwent a cardiac catheterization to rule out ischemic disease, which revealed retrograde contrast flow through the left coronary artery from the right coronary artery. A coronary computed tomography (CT) angiogram was pursued which showed the presence of an anomalous left coronary artery arising from the pulmonary artery (ALCAPA). For the management of her atrial fibrillation, she was electrically cardioverted. She was discharged on guideline-directed medical therapy for her heart failure, with a cardiac surgery referral for the surgical fixation of her ALCAPA.